2001
DOI: 10.1093/jnci/93.11.858
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Colorectal Cancer in Stool With the Use of Multiple Genetic Targets

Abstract: We were able to detect the majority of colorectal cancers by analyzing stool DNA for just three genetic markers. Additional work is needed to determine the specificity of these genetic tests for detecting colorectal neoplasia in asymptomatic patients and to more precisely estimate the prevalence of the mutations and sensitivity of the assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
148
0
10

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(163 citation statements)
references
References 22 publications
5
148
0
10
Order By: Relevance
“…HIF-1 is stabilised by p53 mutations (Kress et al, 1998;Ravi et al, 2000). Indeed, mutations in the ras oncogene and p53 antioncogene are detectable in 40 -60% of colorectal cancers (Bos, 1989;Kinzler and Vogelstein, 1996;Dong et al, 2001;Rengucci et al, 2001;Nishikawa et al, 2002;Smith et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 is stabilised by p53 mutations (Kress et al, 1998;Ravi et al, 2000). Indeed, mutations in the ras oncogene and p53 antioncogene are detectable in 40 -60% of colorectal cancers (Bos, 1989;Kinzler and Vogelstein, 1996;Dong et al, 2001;Rengucci et al, 2001;Nishikawa et al, 2002;Smith et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) is of proven benefit in prognosis and follow-up, but has limited sensitivity (30 -40%) for early CRC (Fletcher, 1986), whereas serial faecal occult blood testing is proven to reduce CRC mortality but suffers from significant false-negative and falsepositive rates (Hardcastle et al, 1989;Mandel et al, 1993;Kronberg et al, 1996). Stool DNA analysis for multiple targets has shown sensitivity of 71 -91% in preliminary studies and larger studies are underway (Ahlquist et al, 2000;Dong et al, 2001); however, a serum-based assay with equivalent sensitivity and specificity would be more acceptable to many patients.…”
mentioning
confidence: 99%
“…9,[11][12][13][14][15][16][17][18] The reliability of DNA amplification shown by our QRTPCR assay indicates that DNA isolated from material obtained with the new collection technique is of much higher quality than widely used DNA extracted from stool.…”
Section: Early Detection and Diagnosismentioning
confidence: 92%
“…Purification of human DNA from stool is difficult, [14][15][16] and there is no unique molecular signature reliably indicating cancer presence. The latter difficulty resulted in the use of multimarker assays, 3,9,[11][12][13][14][15][16][17][18] making the cost-effectiveness of the approach a major issue. 9,[19][20][21] It has been suggested that exfoliated colonocytes collected directly from the surface of colonic mucosa could serve for diagnostic and research applications better than stool-derived material.…”
mentioning
confidence: 99%
See 1 more Smart Citation